P349 Sexual behavior and STI risk among MSM and transgender women participating in a study of timing of antiretroviral therapy. (14th July 2019) - Montaño, Michalina; Lama, Javier; Sanchez, Jorge; Gonzales, Pedro; Rios, Jessica; Duerr, Ann
Abstract : Background: We assessed sexual behavior and sexually transmitted disease risk among men who have sex with men and transgender women participating in Sabes, a study of an expanded treatment as prevention strategy focused on early diagnosis and treatment of HIV infection. Methods: Sabes participants were tested monthly for HIV to identify acute or early infections, and HIV-positive participants were randomized to receive ART immediately (Immediate) or after 24 weeks (Deferred) during a 48-week follow-up period. Sexual behavior was assessed via computer-based questionnaire at randomization (baseline) and every 12 weeks thereafter. Participants were tested for urethral and rectal chlamydia and gonorrhea (via nucleic acid amplification tests) and for syphilis at baseline, 12, 24, and 48 weeks. We used generalized estimating equations to describe sexual behavior over 48 weeks for each study arm, and Cox proportional hazards to compare STI risk between arms. Results: After randomization, 209 HIV-positive participants completed at least 12 weeks of study. The number of anal sex partners (in the prior 3 months) declined in both arms (Immediate: 12-week IRR=0.66; 95%CI=0.45–0.97, 48-week IRR=0.75; 95%CI=0.51–1.12; Deferred: 12-week IRR=0.68; 95%CI=0.53–0.88, 48-week IRR=0.56; 95%CI=0.40–0.79). The proportion reporting >50% condom use with main partners (in the prior 30 days) doubled among Deferred participants (12-week RR=2.04; 95%CI=1.40–2.95, 48-week RR=1.97; 95%CI=1.35–2.87) and increased by 75% among Immediate participants (12-week RR=1.75; 95%CI=1.31–2.35, 48-week RR=1.74; 95%CI=1.26–2.41). Condom use with casual partners increased in both arms (Immediate: 12-week RR=1.37; 95%CI=1.16–1.61, 48-week RR=1.23; 95%CI=1.02–1.49; Deferred: 12-week RR=1.47; 95%CI=1.20–1.79, 48-week RR=1.25; 95%CI=0.99–1.58). Relative to Immediate participants, Deferred participants had higher risk of chlamydia (Hazard Ratio=1.85; 95%CI=1.09–3.15), with a trend toward higher risk of gonorrhea (HR=1.62; 95%CI=0.88–2.97), and syphilis (HR=2.05; 95%CI=0.82–5.16). Conclusion: Despite reporting protective behavior at levels similar to or slightly higher than those of participants who started ART immediately, participants who deferred ART initiation had increased risk of bacterial STIs. This warrants further investigation. Disclosure: No significant relationships.